2014
DOI: 10.3390/rs6031783
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns and Climate Variables Controlling of Biomass Carbon Stock of Global Grassland Ecosystems from 1982 to 2006

Abstract: Abstract:Grassland ecosystems play an important role in subsistence agriculture and the global carbon cycle. However, the global spatio-temporal patterns and environmental controls of grassland biomass are not well quantified and understood. The goal of this study was to estimate the spatial and temporal patterns of the global grassland biomass and analyze their driving forces using field measurements, Normalized Difference Vegetation Index (NDVI) time series from satellite data, climate reanalysis data, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 45 publications
1
48
2
1
Order By: Relevance
“…Precipitation also significantly influences the spatial and temporal dynamics of NDVI in which the biomass accumulation follows the precipitation gradient [63]. The variation in vegetation productivity could be linked to either change in vegetation or variation in precipitation distribution.…”
Section: Ndvi Precipitation Correlation Analysismentioning
confidence: 99%
“…Precipitation also significantly influences the spatial and temporal dynamics of NDVI in which the biomass accumulation follows the precipitation gradient [63]. The variation in vegetation productivity could be linked to either change in vegetation or variation in precipitation distribution.…”
Section: Ndvi Precipitation Correlation Analysismentioning
confidence: 99%
“…Overall, the higher temperature, higher precipitation and lower elevation could result in the higher grassland biomass density in the southeast. Previous researches also suggested that carbon storage tended to accumulate in area where climatic factors were suitable (Gao et al, 2013a;Jiang et al, 2014;Kang et al, 2013;Mao et al, 2014;Wang et al, 2014;Xia et al, 2014). Moreover, anthropogenic factor (e.g., forage, fire, green project etc.)…”
Section: Spatial Distribution Of Grassland Biomass and Relative Uncermentioning
confidence: 99%
“…Grassland ecosystems accumulate up to 18% of the total global terrestrial carbon sink each year and play an important role in the global carbon cycle [3]. However, due to global warming and unreasonable human disturbance [4], they grazing regions from the NDVI data and then obtained grazing intensity through the grazing steppe area and annual sheep units [27].…”
Section: Introductionmentioning
confidence: 99%